Temperature change in pig rib bone during implant site preparation by low-speed drilling - Sun-Jong Kim; Jaeyoung Yoo; Young-Soo Kim; Sang-Wan Shin (University of São Paulo, 2010)
OBJECTIVES: The purpose of this study was to evaluate the temperature change during low-speed drilling using infrared thermography. MATERIAL AND METHODS: Pig ribs were used to provide cortical bone of a similar quality to human mandible. Heat production by three implant drill systems (two conventional drilling systems and one low-speed drilling system) was evaluated by measuring the bone temperature using infrared thermography. Each system had two different bur sizes. The drill systems used were twist drill (2.0 mm/2.5 mm), which establishes the direction of the implant, and finally a 3.0 mm-pilot drill. Thermal images were recorded using the IRI1001 system (Infrared Integrated Systems Ltd.). Baseline temperature was 31±1ºC. Measurements were repeated 10 times, and a static load of 10 kg was applied while drilling. Data were analyzed using descriptive statistics. Statistical analysis was conducted with two-way ANOVA. RESULTS AND CONCLUSIONS: Mean values (n=10 drill sequences) for maximum recorded temperature (Max TºC), change in temperature (ΔTºC) from baseline were as follows. The changes in temperature (ΔTºC) were 1.57ºC and 2.46ºC for the lowest and the highest values, respectively. Drilling at 50 rpm without irrigation did not produce overheating. There was no significant difference in heat production between the 3 implant drill systems (p>0.05). No implant drill system produced heat exceeding 47ºC, which is the critical temperature for bone necrosis during low-speed drilling. Low-speed drilling without irrigation could be used during implant site preparation.